Netherlands to open archive on people accused of wartime Nazi collaboration - Boztas, Senay (The Guardian, 2024)
Some descendants are apprehensive but a historian says making 30m pages of records public is ‘important step’.
Keywords: Europe; Holocaust; Netherlands; Second world war; World news

WHO continues to urge China to share data five years after COVID-19 - UN News (UN News, 2024)
“We continue to call on China to share data and access so we can understand the origins of COVID-19,” WHO said. “This is a moral and scientific imperative. Without transparency, sharing, and cooperation among countries, the world cannot adequately prevent and prepare for future epidemics and pandemics. “

How ‘Trophy’ Videos Link Paramilitary Commanders to War Crimes in Sudan - Varghese, Sanjana; Reneau, Natalie; Koettl, Christoph; Byrd, Aaron; Walsh, Declan (The New York Times, 2024)
Visual evidence collected and analyzed over months by The New York Times identifies the commanders leading an opaque paramilitary group, the Rapid Support Forces, as fighters under their watch commit atrocities across Sudan.
Keywords: Darfur (Sudan); International Criminal Court; Nuba Mountains (Sudan); Rapid Support Forces (Sudan); South Kordofan (Sudan); Sudan; Sudanese Armed Forces; your-feed-visual-investigations

Disgruntled police in Northern Ireland responsible for IRA leaks after Good Friday agreement - Booth, Robert (The Guardian, 2024)
Newly released Irish archives include leaks from UK government and RUC’s attempts to undermine Sinn Féin
Keywords: Good Friday agreement; IRA; Ireland; Mo Mowlam; Northern Ireland; Politics; UK news

Massive layoffs endanger dictatorship memorial sites, workers say - Iglesia, Facundo (Buenos Aires Herald, 2024)
Paula Eugenia Donadio, a representative of state-workers union ATE, told the Herald that the layoffs endanger the functioning of dictatorship memorial sites run by the secretariat. The memorials are repurposed former clandestine detention centers that operated during the 1976-1983 military dictatorship. According to human rights organizations, these centers were instrumental in the forcible disappearance of over 30,000 people.

Why speech could be a target for the anti-abortion movement in 2025 - Sherman, Carter (The Guardian, 2024)
The anti-abortion movement is looking at ways to control information about how and where to obtain abortions
Keywords: Abortion; Health; Roe v Wade; Society; US news; Women; World news

From Nuremberg to now: How a war crimes trial in Sweden is changing legal history - Maxim, Julius (Politico, 2024)
Prosecutors are using “universal jurisdiction” to hold companies to account for their operations overseas.

A radical way to teach contested history - Pidd, Helen (The Guardian, 2024)
Helen Pidd visits Lancaster Royal grammar school to see the work of Parallel Histories, an education charity which helps young people make sense of contested history
Keywords: Education; History; Schools

Journalists who were unlawfully spied on have ‘no doubt’ UK reporters are still targeted - Siddique, Haroon (The Guardian, 2024)
Belfast-based Trevor Birney and Barry McCaffrey won landmark victory that PSNI’s surveillance was unlawful
Keywords: Espionage; London; MI5; Media; Metropolitan police; Northern Ireland; Police; UK news; UK security and counter-terrorism; World news

UNAIDS - partnerships for country led and country owned data system: A transformative approach - UNAIDS (UNAIDS, 2024)
​There is an urgent need to address inequities in global health practices, including how data are collected and used. In the case of HIV data, UNAIDS has consistently strived to strengthen partnerships with countries to support them in their data journeys, from collecting to using HIV data.

Entre 1828 et 1970 | Plus de 3000 enfants morts dans des pensionnats autochtones - AFP (La Presse, 2024)
Au moins 3104 enfants autochtones sont morts dans des pensionnats aux États-Unis, arrachés à leur famille pour être assimilés de force.

En Syrie, la Croix-Rouge espère travailler avec les nouvelles autorités du pays sur la recherche des disparus - Hélène Sallon (Le Monde, 2024)
Le Comité international de la Croix-Rouge n’avait pas accès aux lieux de détention gérés par les branches de sécurité du régime, qui pourraient être responsables de la mort de plusieurs centaines de milliers de Syriens.

A Billion Lives Off the Record: The Urgent Need for Legal Identity - Baher Kamal (Inter Press Service, 2024)
Over one billion people worldwide lack legal identity, leaving them unable to access basic rights and services like healthcare, education, and voting

Brazil Bans X from Using Children to Power Its AI - Han, Hye Jung (Human Rights Watch, 2024)
This week, Brazil’s National Data Protection Authority banned the social media platform X, formerly Twitter, from using the personal data of its child users in Brazil to train its artificial intelligence (AI).
Keywords: Technology

End Prosecutions Targeting Kurdish Language Activities in Türkiye - Hugh Williamson (Human Rights Watch, 2024)
Rıfat Roni has spent more than a decade as an official court interpreter facilitating communication for Kurdish speakers in legal proceedings. This week, he found himself in the dock facing charges.

Rights investigators call for protection of evidence, including mass grave sites - Vibhu Mishra (UN News, 2024)
In a landmark mission to Syria, the UN probe into the most serious rights violations committed in the country since 2011 has called on caretaker authorities to take immediate measures to protect mass grave sites and preserve critical evidence.

Special Rapporteur on Torture documents Syrian violations for ICJ case - OHCHR (OHCHR, 2024)
There is a danger that important evidence of torture and other crimes is being lost in Syria, as families of missing people desperately seek news of their loved ones, the UN Special Rapporteur on Torture, Alice Jill Edwards warned today.

Security Council Debates Use of Artificial Intelligence in Conflicts, Hears Calls for UN Framework to Avoid Fragmented Governance - United Nations (UN Meetings Coverage and Press Releases, 2024)
Rapidly evolving artificial intelligence (AI) is outpacing human ability to govern it, even threatening human control over weapons systems, the United Nations chief warned during a Security Council briefing today, urging Member States to swiftly establish “international guard-rails” to ensure a safe, secure and inclusive AI future for all. “Artificial intelligence is not just reshaping our world — it is revolutionizing it,” underscored Secretary-General António Guterres. AI tools are identifying food insecurity and predicting displacements caused by extreme events and climate change, detecting and clearing landmines, and soon will be able to spot patterns of unrest before violence erupts.

Humanity’s fate can’t be left to algorithms, UN chief tells Security Council - Vibhu Mishra (UN News, 2024)
The UN Secretary-General on Thursday urged the Security Council to act decisively to establish international guardrails for artificial intelligence (AI), warning that delays could heighten risks to global peace and security.

Bulgaria trying to force out Syrian asylum seekers after fall of Assad - Tondo, Lorenzo; Kassam, Ashifa (The Guardian, 2024)
NGO finds Syrians subjected to interrogations and reportedly pressed into signing return documents
Keywords: Bulgaria; Europe; European Union; Refugees; Syria; World news

Bulgaria trying to force out Syrian asylum seekers after fall of Assad - Tondo, Lorenzo; Kassam, Ashifa (The Guardian, 2024)
NGO finds Syrians subjected to interrogations and reportedly pressed into signing return documents
Keywords: Bulgaria; Europe; European Union; Refugees; Syria; World news

Getting serious about AI rules: Lack of enforcement capacity puts EU at risk - Voss, Axel (Euractiv, 2024)
In half a year, common EU rules start to apply to the most advanced AI models, crucial to supporting downstream industry and protecting citizens against systemic risks. The AI Office in the European Commission, however, is massively understaffed for the task, counting so far only around 85 staffers – out of which only around 30 team members are specifically tasked with the implementation of the AI Act.

AI-based-technologies for trustworthy solutions against disinformation - AI4TRUST - Euractiv's Advocacy Lab (Euractiv, 2024)
The AI4TRUST project aims to combat misinformation and disinformation in the EU by creating a trust-based environment that integrates the automated monitoring of social and news media with advanced AI-based technologies to enhance the work of human fact-checkers.

Spain introduces bill to combat online fake news - France-Presse, Agence (The Guardian, 2024)
Minister calls bill demanding digital platforms publicly correct false information ‘good news for democracy’
Keywords: Digital media; Europe; Internet; Media; Pedro Sánchez; Social media; Spain; World news

Commission opens TikTok investigation over Romanian presidential elections disinformation - Hartmann, Théophane (Euractiv, 2024)
The Commission could eventually fine TikTok up to 6% of its global worldwide turnover for failure to comply.

Liberian Warlord-Politician’s Death and the Search for Justice - Michelle Reyes Milk (Human Rights Watch, 2024)
Liberia’s Prince Y. Johnson, who rose to prominence first as a warlord and then politician, was implicated in serious abuses during the country’s two civil wars between 1989 and 2003.

General Assembly Adopts 47 Third Committee Resolutions, including Texts on Nazi Glorification, Children's Rights, Palestine Statehood - United Nations (UN Meetings Coverage and Press Releases, 2024)
The General Assembly adopted 47 draft resolutions and one decision recommended by its Third Committee (Social, Humanitarian and Cultural) today, covering a wide range of issues, from countering violence against children and combating the glorification of Nazism to protecting the rights of Indigenous Peoples and ensuring the right of the Palestinian people to self-determination. The draft on combating the glorification of Nazism contained in report A/79/456 elicited debate, triggering a recorded vote before its adoption. By the text, the Assembly expressed concern about the glorification of the Nazi movement, neo-Nazism and former members of the Waffen SS organization, including by erecting monuments and memorials and holding public demonstrations in the name of the glorification of the Nazi past.

Authorities using spyware and Cellebrite forensic extraction tools to hack journalists and activists - Amnesty International (Amnesty International, 2024)
Serbian authorities are using spyware and Cellebrite forensic extraction tools to hack journalists and activists in a surveillance campaign.

Las autoridades utilizan programas espía y herramientas de extracción forense de Cellebrite para ‘hackear’ a periodistas y activistas - Amnesty International (Amnesty International, 2024)
La policía y las autoridades de los servicios de inteligencia de Serbia están utilizando programas avanzados de espionaje telefónico, junto con productos forenses para teléfonos móviles, para atacar ilegítimamente a periodistas, activistas ambientales y otras personas en una campaña de vigilancia encubierta, según ha revelado un nuevo informe de Amnistía Internacional.

Les autorités utilisent des logiciels espions et les outils criminalistiques d’extraction de données Cellebrite pour pirater des journalistes et des militantes - Amnesty International (Amnesty International, 2024)
Les services de police et du renseignement serbes utilisent un logiciel espion avancé, ainsi que des outils de criminalistique mobile pour cibler illégalement des journalistes, des militant·e·s écologistes et d’autres individus dans le cadre d’une campagne de surveillance secrète, révèle un nouveau rapport d’Amnesty International.

Serbia used Israeli firm’s tech to enable spy campaign, Amnesty says - Euractiv.com with Reuters (Euractiv, 2024)
According to Amnesty, Serbia received phone-cracking devices as part of a broader package of assistance designed to help Serbia meet the requirements for EU accession.

Serbia used Israeli firm’s tech to enable spy campaign, Amnesty says - Euractiv.com with Reuters (Euractiv, 2024)
According to Amnesty, Serbia received phone-cracking devices as part of a broader package of assistance designed to help Serbia meet the requirements for EU accession.

Digital governance in the era of hybrid warfare, with Estonia’s digital minister - Santana, Giada (Euractiv, 2024)
In this episode, host Giada Santana is joined by Estonia's Justice and Digital Affairs Minister Liisa Pakosta to discuss Estonia's digital transformation and the challenges of securing a fully digital state in an era of escalating cyber warfare.

States should ask "Where is Sombath?" at upcoming review of human rights record - International Federation for Human Rights (International Federation for Human Rights, 2024)
On the 12-year anniversary of the unresolved enforced disappearance of Lao civil society leader Sombath Somphone, we, the undersigned civil society organizations and individuals worldwide, urge United Nations (UN) member states to express their concern over this continuing crime and to call for the prompt resolution of Sombath’s case at the upcoming review of the human rights record of Laos.

Restore, destroy or leave to rot? Battle lines drawn over west Africa’s architectural heritage - Egbejule, Eromo (The Guardian, 2024)
Uncompleted or abandoned buildings are a regular feature of the landscape. Now calls for restorations are increasing
Keywords: Africa; Architecture; Art and design; Culture; Togo; World news

35,000 registered missing in 13 years of conflict as ICRC helps families seek answers - International Committee of the Red Cross (International Committee of the Red Cross, 2024)
In the past 13 years, the ICRC has registered 35,000 cases of people who have gone missing in Syria. This number reflects the requests of the families who approached the ICRC - we know that in reality the numbers are far greater.

SOS-defenders platform: Expose arbitrary detention of human rights defenders worldwide - International Federation for Human Rights (International Federation for Human Rights, 2024)
A collective of local, regional and international human rights organisations unveils SOS-Defenders, an action platform that exposes the alarming scale of arbitrary detention of human rights defenders worldwide.

Assad’s Fall in Syria Renews Push for Justice on Crimes Committed by His Regime - Bigg, Matthew Mpoke (The New York Times, 2024)
It seems unlikely that deposed President Bashar al-Assad, who fled to Russia, will be forced to stand trial. That is not deterring activists who have worked for years to document his government’s crimes.
Keywords: Assad, Bashar al-; General Assembly (UN); Human Rights and Human Rights Violations; International Court of Justice (UN); International Criminal Court; Syria; Syrian Network for Human Rights; Syrian Observatory for Human Rights

The 'Smuggler' of Syrian Torture Archives Reveals His True Identity - Camille Tawil (Asharq Al-Awsat, 2024)
For many years, the world only knew them by the aliases Caesar and Sami. Since 2014, these two names have been associated with documenting torture in Syrian prisons. The photos they smuggled out of Syria shook the world and prompted the United States to impose strict sanctions on the regime of former President Bashar al-Assad, under what became known as the “Caesar Act.” These horrific photos documenting torture inflicted on detainees in Syrian prisons were used in courts in Western countries to convict Syrian officers on charges of torture and human rights violations.

Preuves de crimes de guerre en Syrie : "Nous avons 283 terabytes d'informations", explique un membre des Nations unies chargé de la collecte - France Info (France Info, 2024)
Le chef des rebelles islamistes syriens a prévenu qu’il n’y aurait pas d'amnistie pour les personnes impliquées dans la torture des détenus.

Bringing Perpetrators of Gross Human Rights Violations to Task - Groundviews (Groundviews, 2024)
The International Truth and Justice Project (ITJP), an independent NGO working since 2013 to protect and promote justice and accountability in Sri Lanka, has submitted more than 60 sanctions and visa ban requests against public and security officials to date as well as a series of universal jurisdiction cases. These have been sent to the governments of the US, UK, Australia, Canada and the EU as well as the UN. The submissions cover gross violations of human rights and significant corruption in respect of the army, navy, air force, police and intelligence officials, Tamil paramilitaries as well as civil servants including judges and former ministers, a press release from the organization said.

New Laws Threaten Free Expression, Privacy - Human Rights Watch (Human Rights Watch, 2024)
El Salvador’s recently approved cybersecurity and data protection laws contain sweeping provisions that threaten media freedom and privacy rights, Human Rights Watch said today.

The Measure of Time: Using Age Determination to Secure Identity and Civil Documentation - IOM (ReliefWeb, 2024)
Four workstations in a corner office at the Nazal health centre in Fallujah are ready to receive their first applicants. A red ribbon and mint green signs are the only markings for this newly established age determination committee, supported by the International Organization for Migration (IOM) in Iraq, and the Government of France. This committee will open doors to a new life for thousands of Iraqis in Fallujah, 65 km away from the capital, and offer critical services that were previously out of reach for families displaced by the conflict with Daesh.

Slovak ombudsman and opposition to challenge information bill in Constitutional Court - Silenská, Natália (Euractiv, 2024)
The bill could lead to arbitrary decisions and inconsistent treatment of requests for information.

The Bibi Files review – tapes and testimony expose paranoia and petulance of Netanyahu family - Bradshaw, Peter (The Guardian, 2024)
Alexis Bloom’s documentary, which shows the Israeli prime minister and his family under police interrogation over corruption charges, reveals their sense of entitlement
Keywords: Benjamin Netanyahu; Culture; Documentary films; Fatah; Film; Gaza; Hamas; Israel; Middle East and north Africa; Palestinian territories; World news

Ukraine’s death-defying art rescuers - Higgins, Charlotte; Alexandrou, Nicola; Bury, Ellie (The Guardian, 2024)
When Putin invaded, a historian in Kyiv saw that Ukraine’s cultural heritage was in danger. So he set out to save as much of it as he could.
Keywords: Museums; Russia; Sculpture; Ukraine

US should declassify what it knows about deadly Colombian Supreme Court attack - Lauren Harper (Freedom of the Press, 2024)
Declassification diplomacy is one of US government’s most distinctive foreign policy tools, and it should be deployed as often as possible

US should declassify what it knows about deadly Colombian Supreme Court attack - Lauren Harper (Freedom of the Press, 2024)
Declassification diplomacy is one of US government’s most distinctive foreign policy tools, and it should be deployed as often as possible

Key US agency that fights foreign influence in jeopardy after funding snub - Gedeon, Joseph (The Guardian, 2024)
Global Engagement Center targeted by Republicans skeptical of alleged censoring of conservative viewpoints
Keywords: Republicans; US Congress; US foreign policy; US news; US politics

Repeal Harmful Internet Laws - Human Rights Watch (Human Rights Watch, 2024)
The Vietnamese government should repeal a draconian new decree tightening control of internet use and the 2018 Law on Cybersecurity.

Syria’s prison records vital for war crimes evidence - Mahmut Geldi (Anadolu Agency, 2024)
Fadl Abdulghani, head of the Syrian Network for Human Rights (SNHR), emphasized the importance of preserving prison and detention center archives in Syria to uncover the fate of detainees and identify those responsible for torture and other war crimes.

Nicaragua tortured at least 229 political prisoners, rights group says - Reuters (Reuters, 2024)
At least 229 people detained in Nicaragua for political reasons have suffered various forms of torture and other "crimes against humanity" at the hands of the government over the past seven years, a human rights NGO said.

En Syrie, la bataille pour la préservation des preuves des crimes du régime Al-Assad - Stéphanie Maupas (Le Monde, 2024)
Plusieurs organisations demandent à la coalition de rebelles de ne pas détruire les preuves des crimes du régime. De les préserver dans l’espoir d’une justice future et pour aider aussi à la recherche des milliers de disparus dans les geôles des Al-Assad.

Trump first-term inquiry into leakers led to invasive searches, report finds - Tait, Robert (The Guardian, 2024)
Justice department says lawyers overreached in aiming to discover who was leaking classified information in 2017
Keywords: Donald Trump; House of Representatives; Law (US); US news; US politics

UN war crimes tribunals continue to address legacy cases, support national efforts - Vibhu Mishra (UN News, 2024)
The mechanism to complete the work of UN war crimes tribunals continues to make progress in delivering justice for the most serious crimes in Rwanda and the States of the former Yugoslavia, top officials told the Security Council on Tuesday.

Records Seized by Israel Show Hamas Presence in U.N. Schools - Becker, Jo; Rasgon, Adam (The New York Times, 2024)
While Israel asserts that the United Nations has tried to minimize the problem, the global organization says Israeli officials are waging an unfair campaign to discredit it.
Keywords: Gaza Strip; Hamas; Israel; Lazzarini, Philippe (1964- ); Palestinians; Teachers and School Employees; United Nations Relief and Works Agency

Records Seized by Israel Show Hamas Presence in U.N. Schools - Becker, Jo; Rasgon, Adam (The New York Times, 2024)
While Israel asserts that the United Nations has tried to minimize the problem, the global organization says Israeli officials are waging an unfair campaign to discredit it.
Keywords: Gaza Strip; Hamas; Israel; Lazzarini, Philippe (1964- ); Palestinians; Teachers and School Employees; United Nations Relief and Works Agency

Police unlawfully storing images of innocent people for facial recognition - Ungoed-Thomas, Jon (The Observer, 2024)
Privacy fears raised as report warns photographs of arrested people who are then released are being retained.
Keywords: Facial recognition; Police; Privacy; UK news

National Archives digitize cold cases of Black American murders - Russell Contreras (Axios, 2024)
An Axios review of a new National Archives portal found just three digitized unsolved cases of lynchings, racial violence and murders of Black Americans, spawning several decades. The Civil Rights Cold Case Records Collection portal is the federal agency's latest attempt to index civil rights violations and provide a subject guide, part of an aim spelled out by law to bring justice to the victims in those cases.

AI in War and Propaganda: Anna Mysyshyn on Disinformation, Democracy, and Digital Governance - Jacobsen, Scott Douglas (International Policy Digest, 2024)
Anna Mysyshyn explores the transformative role of AI in modern warfare and propaganda, highlighting its threats to democracy and strategies for resilience.

Hungary spied on EU officials, Belgian media reports - Wallace, Nicholas (Euractiv, 2024)
A joint report alleges that Hungarian intelligence searched EU officials' hotel rooms, and stole data from laptops.

A massive database of evidence, compiled by a historian, documents Israel's war crimes in Gaza - Hasson, Nir (Haaretz, 2024)
The report Dr. Mordechai has compiled online – "Bearing Witness to the Israel-Gaza War" – constitutes the most methodical and detailed documentation in Hebrew (there is also an English translation) of the war crimes that Israel is perpetrating in Gaza. It is a shocking indictment comprised of thousands of entries relating to the war, to the actions of the government, the media, the Israel Defense Forces and Israeli society in general. The English translation of the seventh, and to date latest version of the text, is 124 pages long and contains over 1,400 footnotes referencing thousands of sources, including eyewitness reports, video footage, investigatory materials, articles and photographs.
Keywords: Gaza; IDF; Israel war crimes; Israel-Gaza War; Palestinians

Nigeria: Amnesty International petitions ICC judges to end Prosecutor’s delaying of justice for atrocity crimes - Amnesty International (Amnesty International, 2024)
Amnesty International today submitted a legal filing to the Pre-Trial Judges of the International Criminal Court (ICC) on behalf of several victims’ networks, to request an end to the ICC Prosecutor’s indefinite and unfathomable delay to the start of the court’s investigation into war crimes and crimes against humanity in Nigeria.

Enfants métis du Congo : « La Belgique, enfin, accepte de regarder en face son passé colonial » - Colette Braeckman (Le Soir, 2024)
L’Etat belge a été condamné pour crimes contre l’humanité ce lundi, dans l’affaire des enfants métis du Congo. Cinq femmes ont obtenu gain de cause pour avoir été enlevées de force à leur famille.

Enfants métis du Congo : « La Belgique, enfin, accepte de regarder en face son passé colonial » - Colette Braeckman (Le Soir, 2024)
L’Etat belge a été condamné pour crimes contre l’humanité ce lundi, dans l’affaire des enfants métis du Congo. Cinq femmes ont obtenu gain de cause pour avoir été enlevées de force à leur famille.

A North Korean Voice That Kim Jong-un Would Like to Silence - Sang-Hun, Choe (The New York Times, 2024)
Kim Seongmin, who fled to South Korea in the 1990s, broadcasts to his homeland twice a day, delivering the kind of information Pyongyang is trying hard to suppress.
Keywords: Censorship; Content Type: Personal Profile; Defectors (Political); Free North Korea Radio; International Relations; Kim Jong-un; Kim Seongmin; North Korea; Politics and Government; Propaganda; Radio; South Korea

Hawaii Archives shed light on Pearl Harbor Memorial efforts - Kayli Pascal-Martinez (Island News, 2024)
As the anniversary of the attack on Pearl Harbor is right around the corner, December 7, 1941, some documents at the Hawaii State Archives help to shed light on that part of Hawaii’s history and the state’s efforts to honor the war dead.

Sénégal: Thiaroye 1944, un long désir de vérité - Laurent Correau (RFI, 2024)
Il y a 80 ans s’écrivait l’une des pages tragiques de l’histoire franco-africaine : l’armée française ouvrait le feu sur ses propres hommes, des tirailleurs regroupés dans le camp de Thiaroye au Sénégal. Quatre-vingts ans plus tard, une partie de ce qui s’est passé reste encore dans l’ombre. Les proches des disparus demandent une reconnaissance officielle de ce qui s’est passé et de l’innocence de leurs parents. Des historiens réclament un accès plus ouvert aux archives. Les autorités françaises, elles, marquent une nouvelle étape dans le processus de mémoire en reconnaissant qu’un massacre a bien eu lieu à Thiaroye, le 1er décembre 1944.

Sénégal: Thiaroye 1944, un long désir de vérité - Laurent Correau (RFI, 2024)
Il y a 80 ans s’écrivait l’une des pages tragiques de l’histoire franco-africaine : l’armée française ouvrait le feu sur ses propres hommes, des tirailleurs regroupés dans le camp de Thiaroye au Sénégal. Quatre-vingts ans plus tard, une partie de ce qui s’est passé reste encore dans l’ombre. Les proches des disparus demandent une reconnaissance officielle de ce qui s’est passé et de l’innocence de leurs parents. Des historiens réclament un accès plus ouvert aux archives. Les autorités françaises, elles, marquent une nouvelle étape dans le processus de mémoire en reconnaissant qu’un massacre a bien eu lieu à Thiaroye, le 1er décembre 1944.

Chief archivist apology to survivors of abuse in care - New Zealand Archives (New Zealand Archives, 2024)
The Chief Archivist Anahera Morehu sincerely apologises on behalf of Te Rua Mahara o te Kāwanatanga Archives New Zealand (previously the National Archives) for failing to effectively monitor Government recordkeeping

Les commissaires à l’information et les ombuds du Canada adoptent une résolution conjointe réclamant une transparence accrue dans les opérations gouvernementales - Commissaires à l’information du Canada (Information Commissioner of Canada, 2024)
Dans une résolution conjointe, les commissaires à l’information et les ombuds fédéral, provinciaux et territoriaux demandent à leurs gouvernements respectifs de donner la priorité à la transparence dès les premières étapes de la conception de nouveaux systèmes, processus administratifs, procédures et modèles de gouvernance. Cette résolution reflète la nécessité d’adopter une nouvelle norme eu égard aux services gouvernementaux et un engagement collectif à favoriser une culture de transparence et de responsabilité à tous les ordres de gouvernement au Canada.

Canada’s Information Commissioners and Ombuds issue joint resolution calling for enhanced transparency in government operations - Information Commissioner of Canada (Information Commissioner of Canada, 2024)
In a joint resolution, Canada’s Information Commissioners and Ombuds from federal, provincial, and territorial jurisdictions are pressing their respective governments to prioritize transparency in the design and implementation of new systems, administrative processes, procedures, and governance models. This resolution reflects the need for a new standard in government operations and a collective commitment to fostering a culture of transparency and accountability across all levels of government in Canada.